IMPORTANT FACTORS FOR USING THE GEOGEBRA PROGRAM IN TEACHING ANALYTICAL GEOMETRY - Nurmakhanov Kayrat Erpayizovich (Galaxy International Interdisciplinary Research Journal, 2022)
In this article, there is a need to create a set of ready-made models, a system of exercises and tasks for students in accordance with methodological recommendations for studying some topics and sections of the school curriculum in mathematics. It is considered that GeoGebra software can be used as an important tool in forming analytical geometry concepts for students